Contrast – a lightweight Python framework for beamline orchestration and data acquisition. (8th June 2021) - Björling, Alexander; Weninger, Clemens; Kahnt, Maik; Kalbfleisch, Sebastian; Johansson, Ulf; Sala, Simone; Lenrick, Filip; Thånell, Karina
Abstract : Contrast, a simple Python framework for controlling beamline experiments, is presented. Contrast can be easily adapted to any beamline, or serve as inspiration for constructing new, suitable tools tailored to individual instruments. Abstract : The emergence of fourth‐generation synchrotrons is prompting the development of new systems for experimental control and data acquisition. However, as general control systems are designed to cover a wide set of instruments and techniques, they tend to become large and complicated, at the cost of experimental flexibility. Here we present Contrast, a simple Python framework for interacting with beamline components, orchestrating experiments and managing data acquisition. The system is presented and demonstrated via its application at the NanoMAX beamline of the MAX IV Laboratory.